2021
DOI: 10.1101/2021.08.30.458209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An accelerated thrombosis model for computational fluid dynamics simulations in rotary blood pumps

Abstract: Thrombosis is one of the major complications in blood-carrying medical devices and a better understanding to influence design of such devices is desirable. Over the past years many computational models of thrombosis have been developed. However, open questions remain about the applicability and implementation within a pump development process. The aim of the study was to develop and test a computationally efficient model for thrombus risk prediction in rotary blood pumps. We used a two-stage approach to calcul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Larger clearance not only reduces visocus stress inside the clearance, but also cause stronger secondary ows. Furthermore, as some recent studies showed (Olia 2023;Blum et al 2023), contemporary blood pumps are consistently used across a large operating range, and not just solely clustered around their optimal design point, with majority of off-design operation is at lower ow rates, across all patient size populations (not just pediatrics). Lower ow rates lead to longer blood exposure times in current rotary blood pumps withevidence of clinical implications.…”
Section: Discusson and Conclusionmentioning
confidence: 99%
“…Larger clearance not only reduces visocus stress inside the clearance, but also cause stronger secondary ows. Furthermore, as some recent studies showed (Olia 2023;Blum et al 2023), contemporary blood pumps are consistently used across a large operating range, and not just solely clustered around their optimal design point, with majority of off-design operation is at lower ow rates, across all patient size populations (not just pediatrics). Lower ow rates lead to longer blood exposure times in current rotary blood pumps withevidence of clinical implications.…”
Section: Discusson and Conclusionmentioning
confidence: 99%
“…Its calculation method is shown in Equation 7. An accelerated thrombus formation model is utilized to quantitatively assess the thrombus risk (27). This model includes three convection-diffusion equations (Equations 8-10), describing the generation and transport of non-activated platelets (NP), activated platelets (AP), and adenosine diphosphate (ADP).…”
Section: Thrombus Risk Assessment Modelmentioning
confidence: 99%